Little words, big meaning – Ideational and pragmatic markers in fictional war discourse - Zasiekin, Serhii (Lesya Ukrainka Volyn National University, 2025)
War discourse has gained importance amid today’s global instability due to war-related trauma. Because war often involves trauma, its fictional representation may disrupt language coherence. Discourse coherence, marked by specific linguistic cues, helps readers connect ideas. Without such markers, structure remains implicit, potentially hindering interpretation. From this perspective, ideational and pragmatic discourse markers − little linguistic items that structure and organise text − are vital. These connectives have “procedural meaning” (Blakemore, 2002), guiding readers towards comprehension with less cognitive effort. This article examines how such words function in fictional non-war and war discourse. Using the Ukrainian version of LIWC2015 and a Welch Two-Sample t-test in R, based on the specific weights of categories in the two sets of texts, it was possible to identify markers of trauma discourse in Bohdan Lepky’s wartime stories. The results showed that war fiction had a statistically significant reduction in both ideational and discourse-pragmatic markers of coherence. Additionally, there was a trend towards higher lexical density and the use of ‘tentative’ words, or ‘mitigation’ pragmatic markers, and ‘affect’ words, including indicators of anxiety with a focus on the present. These findings offer new insights into how discourse and other pragmatic markers shape the representation of traumatic experiences in the works of individual authors or fictional characters.
Keywords: LIWC; fictional war discourse; ideational markers; discourse markers; pragmatic markers; procedural meaning; Bohdan Lepky